Pathologic basis of coronavirus disease 2019 (COVID-19) - An overview of cellular affinities, pathogenesis, clinical manifestations, autopsy findings and sequelae - Ochuko Orakpoghenor; Talatu Patience Markus; Jamila Abdulhamid Atata; Juwon Pius Erin; Olushola Samuel Olaolu; Collins Chimezie Udechukwu; Ngozi Ejum Ogbuagu; Kelvin Olutimilehin Jolayemi; Magdalene Ogbonneya Okoronkwo; Bala Ningi Umar (Annals of Cytology and Pathology - Peertechz Publications, 2020)
The global terror instigated by coronavirus disease 2019 (COVID-19) cannot be underestimated and the need for drastic measures towards its control cannot be overemphasized. Coronavirus disease 2019 is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) following attachment of the virus to specific receptors in the body. The distribution of these specialized receptors in various organs and tissues of the body is responsible for the various clinical presentations associated with the disease after infection. Despite the higher risk of spread of the infection, autopsies have been carried out though with maximum precautionary measures and information provided to further elucidate the extent of damages caused by the disease. Pathologic mechanisms leading to death from COVID-19 include respiratory failure due to surfactant deficiency and consequent alveolar collapse, cardiac syncope from direct damage to cardiac muscles, peripheral paralysis, cytokine storm and excessive haemorrhage from impaired coagulation. In patients that recover, potential outcomes which could be short- and/or long-term have been recognized. As a means to develop effective control, eradication and prevention strategies, a proper understanding of the mechanisms of SARS-CoV-2 infection will fully ensure a positive breakthrough. Hence, in this article, the pathologic basis of COVID-19 are provided based on extensive literature searches, and proposed mechanisms of pathogenesis, clinical manifestations, autopsy findings and sequelae are being described.